Anti-adhesion and antibiotic modulatory evaluation of grapefruit (Citrus paradisi) juice and seed extract on bacteria isolated from urine and catheter - Michael Oluwole Osungunna; Grace O. Onawunmi (GarVal Editorial Ltda., 2016)
Context: The in vivo use of grapefruit seed in the treatment of urinary tract infections (UTIs) has been reported but the mechanism of action is yet to be explained. Aims: Evaluate the anti-adhesion and antibiotic modulatory activities of grapefruit seed extract and juice as their possible mechanisms of action. Methods: Sub-inhibitory concentrations of 2.5 and 5 mg/mL as well as 10.3 and 5.15 mg/mL of grapefruit seed extract and juice respectively were evaluated for modulatory activity of ciprofloxacin, streptomycin and nalidixic acid against one hundred and twenty seven bacterial isolates from mid-stream urine (MSU) (100), catheter-stream urine (CSU) (14) and catheter tips (CT) (13) using the agar dilution method. Anti-adhesion activity of grapefruit seed extract and juice at sub-inhibitory concentrations of 2.5 and 1.03 mg/mL respectively was evaluated against twenty three (23) moderately adherent bacterial isolates from MSU (10), CSU (7) and CT (6) using the tissue culture plate method. Results: The results revealed that grapefruit juice (5.15 mg/mL) showed more effect on nalidixic acid activity than seed extract (2.5 mg/mL). Grapefruit juice showed more anti-adhesion activity than grapefruit seed extract at the concentration tested. Conclusions: The study concluded that grapefruit seed extract and juice had anti-adhesion and antibiotic modulatory effects on bacteria associated with UTIs.